MERDEKA (MEDIA PEMBELAJARAN DENGAN SAMPAH PLASTIK) UNTUK KELAS VI B DI UPT SPF SD INPRES BONTOMANAI - Nurjannah K; Klara Taruk Kambong; Nurul Hidayah Ilyas; Muh Ashar A Irsyad; Mutmainnah M; Nunu Alwiyah; Nur Hikmah; Miranda Astari; Putri Andani Irwan; Nur Wahyuni; Rahmatia Thahir; Munawwarah Thalib (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Learning media can originate from the utilization of plastic waste, which is an innovative step to enhance environmental awareness among students. This article outlines a community service activity conducted in Class VI B at UPT SPF SD Inpres Bontomanai, titled "Learning Media with Plastic Waste." The primary objective of this activity is to educate students about the importance of recycling and reusing plastic waste in their daily lives. The process begins with the collection of plastic waste around the school, followed by guidance that involves students in recycling that waste into teaching aids and environmentally friendly learning media. The active involvement of students not only teaches them recycling techniques but also cultivates their creative skills and teamwork. The results of this activity show an increase in student creativity and their understanding of important environmental issues. Feedback from teachers and students has been very positive, indicating that this learning method is considered innovative and beneficial. It is hoped that this activity can serve as a model for other schools in integrating environmental education into their curricula. By utilizing local resources such as plastic waste, schools can encourage students to be more active in preserving nature. This aligns with sustainable development goals, particularly in the fields of education and waste management, which are crucial for a better future.